METODE UJI KETELITIAN UNJUK KERJA ALAT UKUR DENGAN PENERAPAN PERSAMAAN DISTRIBUSI NORMAL (CONTOH KASUS LASER DOPPLER ANEMOMETER) - Laksitaningtyas, Agatha Padma; Legono, Djoko; Yulistiyanto, Bambang (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p10, 2020)
Statistics and probability is one of the methods used in digital signal processing to measure.  Digital signal processing functions to measure, classify and process into data component that offend an object. Determining the ratio of signal power to noise at the reception of input and output systems is very important to estimate the quality and capacity of signal reception from an instrument Laser Doppler Anemometer (LDA) device. LDA is an example of a measuring instrument that functions to measure the speed that will issue frequencies so as to produce a signal. The basic problem in signal measurement is how to distinguish the true fundamental signal from noise. The purpose of this study is to test the accuracy testing of the performance of a measuring tool to determine the noise from a signal issued by an LDA. The analysis used is using the normal distribution equation which will produce a boundary value for the signal and noise. The test is carried out on two open channels in the laboratory in the form of U and S shaped channels. In U Channel there are four test points, while for S Channel there are eight test points. For each point was done three times testing. The accuracy test of the LDA signal reading shows that the frequency of the signal reading on the U channel is 92.47% with a noise value of 7.53%. The accuracy test of the LDA signal reading shows the signal reading frequency on the S channel is 93.74% with a noise value of 6.26%.